2019
DOI: 10.1248/bpb.b19-00044
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Rocuronium-Induced Deep Neuromuscular Block with Sugammadex in Infants and Children—A Randomized Study

Abstract: Sugammadex 4 mg•kg 1 is recommended for reversal from rocuronium-induced deep neuromuscular block. However, there is limited data regarding the dose-response of sugammadex required for reversal from deep neuromuscular block in pediatric patients. The aim of this study was to determine the reversibility of rocuronium-induced deep neuromuscular block with sugammadex in infants and children. Seventy-five children (48 infants and 27 children, mean standard deviation (S.D.), age: 11.6 (6.7) months) were enrolled in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…The incidence of TOFR decreasing to < 0.9 after it had been reversed to ≥0.9 via sugammadex administration (2.0 mg•kg − 1 ) was not observed in any of the patients aged 1-12 years. A previous study reported that no difference in recovery was observed between the use of 2.0 mg•kg − 1 and 4.0 mg•kg − 1 sugammadex to reverse rocuronium-induced deep neuromuscular blockade from the re-appearance of post-tetanic count to a TOFR of 0.9 in infants and children [9]. This indicates that 2.0 mg•kg − 1 sugammadex may be sufficient to fully reverse rocuronium-induced moderate neuromuscular blockade in pediatric patients aged 1-12 years.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The incidence of TOFR decreasing to < 0.9 after it had been reversed to ≥0.9 via sugammadex administration (2.0 mg•kg − 1 ) was not observed in any of the patients aged 1-12 years. A previous study reported that no difference in recovery was observed between the use of 2.0 mg•kg − 1 and 4.0 mg•kg − 1 sugammadex to reverse rocuronium-induced deep neuromuscular blockade from the re-appearance of post-tetanic count to a TOFR of 0.9 in infants and children [9]. This indicates that 2.0 mg•kg − 1 sugammadex may be sufficient to fully reverse rocuronium-induced moderate neuromuscular blockade in pediatric patients aged 1-12 years.…”
Section: Discussionmentioning
confidence: 93%
“…It can encapsulate rocuronium molecules with high affinity to reverse muscle relaxation induced by steroidal nondepolarizing NMBAs [8]. Matsui M et al reported that 4 mg•kg − 1 of sugammadex can provide a complete and rapidly facilitated recovery from rocuronium-induced deep neuromuscular blockade to a TOFR of 0.9 in infants and children [9]. To date, pediatric studies are limited and have focused on using sugammadex to reverse neuromuscular blockade in pediatric patients aged 2-18 years [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of thyroid diseases is increasing, and surgery is the most common treatment (22)(23)(24). In case of recurrent laryngeal nerve injury, should be done immediately.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to sugammadex which encapsulate rocuronium effectively leading to clearance of rocuronium molecules from the neuromuscular junction, liberating nicotinic acetylcholine receptors and restoring neuromuscular transmission. [ 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%